Pertubuhan Jamaah Islah Malaysia and good governance (1991-2012) - Malik, Maszlee (Universiti Sains Islam Malaysia, 2017)
Good Governance Agenda promoted by international institutions and other aid agencies as part of the globalisation phenomenon, proposes amongst others, the active role of a civil society as part of the process towards development. The effective functioning of a civil society is believed to be facilitate the achievement of good governance. Currently, the dynamism of global civil society movements has shifted to a new dimension to incorporate culture and faiths into the discourse on development, economy, politics and governance in a more progressive approach. This paper will try to explore the role of faith in mobilizing civil society towards the achievement of what is known as 'good governance' in Malaysia by looking into Pertubuhan Jamaah Islah Malaysia (JIM) as its case study.